1985
DOI: 10.1177/0148607185009006701
|View full text |Cite
|
Sign up to set email alerts
|

Hand Grip Strength—A Simple Prognostic Indicator In Surgical Patients

Abstract: This study evaluates hand grip strength as an indicator of nutritional status and a predictor of postoperative complications. Hand grip strength and other parameters of nutritional status, namely, midarm muscle circumference, forearm muscle circumference, triceps skinfold, percentage ideal body weight, serum albumin, and percent usual weight were determined preoperatively in 205 patients. Complications occurred in 28 patients (14%). Patients with at least one abnormal nutritional parameter had a higher inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 11 publications
1
47
0
2
Order By: Relevance
“…As expected, improved performance of HGS as a screening method was found for the patients with lower strength (allocated in the first quartile) with higher sensitivity than specificity and also with higher negative predictive values, than when higher cutoff values for HGS (second and third quartiles) were used. This diagnostic value of HGS against NRS-2002 was comparable with some studies carried out in surgical patients using HGS vs more detailed nutritional assessment (Klidjian et al, 1980(Klidjian et al, , 1982Hunt et al, 1985;Kalfarentzos et al, 1989;Webb et al, 1989). The diagnostic value of HGS against NRS-2002 was comparable to that of NRS-2002 and other tools for nutritional screening and assessment at hospital admission (Kyle et al, 2005a;Valero et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As expected, improved performance of HGS as a screening method was found for the patients with lower strength (allocated in the first quartile) with higher sensitivity than specificity and also with higher negative predictive values, than when higher cutoff values for HGS (second and third quartiles) were used. This diagnostic value of HGS against NRS-2002 was comparable with some studies carried out in surgical patients using HGS vs more detailed nutritional assessment (Klidjian et al, 1980(Klidjian et al, , 1982Hunt et al, 1985;Kalfarentzos et al, 1989;Webb et al, 1989). The diagnostic value of HGS against NRS-2002 was comparable to that of NRS-2002 and other tools for nutritional screening and assessment at hospital admission (Kyle et al, 2005a;Valero et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…Muscle strength, measured by handgrip dynamometry, has been shown to be both sensitive and specific in predicting outcome in surgical patients (Klidjian et al, 1982;Hunt et al, 1985;Kalfarentzos et al, 1989;Webb et al, 1989;Pieterse et al, 2002;Bunout et al, 2004;Mahalakshmi et al, 2004), and cirrhotic patients (Á lvares-da-Silva and Da Silveira 2005), as well as being associated with higher long-term mortality (Newman et al, 2006). HGS is also useful for the detection of functional status (Humphreys et al, 2002) and in the onset of activities of daily living (ADL) dependence in the elderly (Rantanen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[34] A study of 205 patients undergoing general surgery also found that those with decreased muscle strength developed significantly more postoperative complications and had increased length of hospital stay than the patients with adequate muscle strength. [35] Additionally, higher muscle strength on admission has been associated with increased likelihood of discharge to usual residence in a study of 120 older adults. [36] …”
Section: Hospitalizationsmentioning
confidence: 99%
“…These tests are inexpensive and easy to perform but may be difficult in the ICU 32,36,37 . Severely malnourished patients will have reduced grip strength 22 .…”
Section: Reduced Grip Strengthmentioning
confidence: 99%
“…Severely malnourished patients will have reduced grip strength 22 . Two studies have correlated handgrip and muscle dynamometry measurement with nutritional status, although the contribution of disease and injury to muscle strength was not measured within the studies 36,37 . The assessment of range of motion of upper extremities can evaluate ability of patients to feed independently and may provide information regarding problems with energy intake in patients [35][36][37][38] .…”
Section: Reduced Grip Strengthmentioning
confidence: 99%